Aromatic polyether ketone molded body and production method therefor
Patent Information
- Application Number
- JP2022073067
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2022-04-27
- Publication Date
- 2025-02-19
- Estimated Expiration
- 2042-04-27
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an aromatic polyether ketone molded body that can be used for various parts and a method for producing the same.
Background Art
[0002] In the field of industrial machinery, there is a demand for replacing metal parts with resin molded bodies from the viewpoint of weight reduction. For the production of such resin molded bodies, for example, super engineering plastics having particularly excellent heat resistance and mechanical strength, typified by polyether ether ketone (PEEK), are used (see, for example, Patent Document 1).
Prior Art Documents
Patent Documents
[0003]
Patent Document 1
Summary of the Invention
Problems to be Solved by the Invention
[0004] In a resin molded body, rapid cooling of the mold after molding is necessary to shorten the cycle time. However, rapid cooling of the mold tends to cause a decrease in the strength near the surface where the progress of crystallization is easily hindered. In order to sufficiently advance the crystallization near the surface of the resin molded body, heat treatment such as annealing treatment can be performed on the resin molded body.
[0005] However, by applying heat treatment to the resin molded body, in addition to increasing the cycle time, a large amount of power is required, so the manufacturing cost of the resin molded body increases. In addition, a large dimensional change due to overall shrinkage occurs in the resin molded body during heat treatment. Therefore, design of a mold or the like taking into account the dimensional change due to heat treatment is required.
[0006] In view of the above circumstances, the present invention aims to provide a technology that can achieve further improvement in the performance of aromatic polyether ketone molded articles. [Means for solving the problem]
[0007] To achieve the above objective, an aromatic polyether ketone molded article according to one embodiment of the present invention comprises a main body and a surface layer covering the main body. In either the main body or the surface layer, measurements using an infrared spectrophotometer revealed a wavenumber of 1295-1340 cm⁻¹. -1 Peak A appears in the range of 1265-1295 cm. -1 An infrared absorption spectrum is obtained that includes peak B, which appears in the range of . The ratio A' / B' of the intensity A' of peak A to the intensity B' of peak B is higher in the surface layer than in the main body.
[0008] In this aromatic polyether ketone molded body, the crystallinity of the surface layer is higher than that of the main body layer inside the surface layer. As a result, high mechanical strength is obtained in the surface layer of this aromatic polyether ketone molded body, which suppresses the progression of wear and the occurrence of chipping. On the other hand, in this aromatic polyetherketone molded body, shock absorption is maintained in the main body portion where the degree of crystallinity is not increased, so the impact applied to the surface layer is absorbed by the main body. As a result, in this aromatic polyetherketone molded body, large localized stresses are less likely to be applied to the surface layer, and the occurrence of damage can be further suppressed.
[0009] The above aromatic polyetherketone molded article may be formed from at least one of a polyetheretherketone and a polyetherketone. The above-mentioned aromatic polyether ketone molded article may be formed from an aromatic polyether ketone containing an additive. The above-mentioned aromatic polyetherketone molded body may be configured as a sliding member. The above-mentioned aromatic polyetherketone molded body may be configured as a gear component.
[0010] A method for producing an aromatic polyether ketone molded article according to one embodiment of the present invention is measured by infrared spectrophotometer at wavenumbers 1295 to 1340 cm². -1 Peak A appears in the range of 1265-1295 cm. -1 The process includes the steps of: producing a molded body from which an infrared absorption spectrum is obtained that includes peak B appearing in the range of ; and irradiating the surface of the molded body with an electron beam. In the electron beam irradiation step described above, the ratio A' / B' of the intensity A' of peak A to the intensity B' of peak B in the surface layer of the molded body may be increased. In the step of irradiating with an electron beam as described above, the molded body may be heated. In these configurations, electron beam irradiation can selectively increase the crystallinity of only the surface layer constituting the surface of the aromatic polyether ketone molded body. [Effects of the Invention]
[0011] As described above, the present invention provides a technology that can achieve further improvement in the performance of aromatic polyether ketone molded articles. [Brief explanation of the drawing]
[0012] [Figure 1] This is a flowchart showing a method for manufacturing a resin molded article according to one embodiment of the present invention. [Figure 2] This figure shows an example of the infrared absorption spectrum of the above-mentioned resin molded product. [Figure 3] This graph shows the change in the ratio A' / B' depending on the electron beam irradiation dose. [Figure 4] This is a plan view showing an example in which the above-mentioned resin molded body is configured as a gear component. [Modes for carrying out the invention]
[0013] [Description of aromatic polyether ketone molded products] The present invention relates to an aromatic polyether ketone molded body which is a resin molded body formed of an aromatic polyether ketone. An aromatic polyether ketone is a resin composed of a benzene ring, an ether, and a ketone, and typically, polyether ether ketone (PEEK) having excellent heat resistance and mechanical strength can be mentioned.
[0014] In addition, the aromatic polyether ketone capable of forming the resin molded body of the present invention includes, in addition to PEEK, for example, polyether ketone (PEK), polyether ketone ketone (PEKK), polyether ether ketone ketone (PEEKK), polyether ketone ether ketone ketone (PEKEKK), and the like. Further, the aromatic polyether ketone forming the molded body of the resin of the present invention may have a configuration in which a plurality of types are blended.
[0015] Further, the resin molded body of the present invention may be formed of an aromatic polyether ketone containing an additive. In the resin molded body, further improvement in performance can be achieved by using an additive. Examples of the additive that can be used in the present invention include fibrous fillers, non-fibrous fillers, solid lubricants, and the like.
[0016] Examples of the fibrous additive include carbon fiber, nanocarbon (carbon nanotube and carbon nanowire), glass fiber, and the like. Examples of the non-fibrous filler include graphite, mica, talc, alumina, and the like. Examples of the solid lubricant include polytetrafluoroethylene (PTFE), tetrafluoroethylene / perfluoroalkyl vinyl ether copolymer (PFA), and the like.
[0017] In the present invention, the performance of the resin molded body is improved by controlling the crystallinity of the aromatic polyether ketone constituting the resin molded body. In one embodiment of the present invention, the crystallinity of the aromatic polyether ketone is grasped from an infrared absorption spectrum obtained by measurement using an infrared spectrophotometer.
[0018] Specifically, the infrared absorption spectrum is obtained as a graph with wavenumber on the horizontal axis and absorbance on the vertical axis by measuring absorbance using an infrared spectrophotometer while continuously changing the wavenumber. In this embodiment, the absorbance of the resin molded article is measured at least 1265 to 1340 cm⁻¹. -1 Perform the operation within the range of wavenumbers that include this range.
[0019] The infrared absorption spectra of aromatic polyether ketones include wavenumbers 1295–1340 cm⁻¹. -1 Peak A appears in the range of 1265-1295 cm. -1 Peak B, which appears in the range, is included. In aromatic polyether ketones, the higher the degree of crystallinity, the higher Peak A becomes relative to Peak B.
[0020] Therefore, the degree of crystallinity of aromatic polyetherketones can be evaluated by the ratio A' / B', which is the ratio of intensity A' obtained as the height of peak A to intensity B' obtained as the height of peak B. In other words, for aromatic polyetherketones, a larger ratio A' / B' indicates a higher degree of crystallinity, and a smaller ratio A' / B' indicates a lower degree of crystallinity.
[0021] Figure 1 is a flowchart showing the method for manufacturing a resin molded article according to this embodiment. First, in step S01 of the manufacturing method according to this embodiment, a raw material resin is prepared. As the raw material resin prepared in step S01, for example, a commercially available product consisting of aromatic polyether ketone pellets or powder can be used.
[0022] Next, in step S02, the raw resin prepared in step S01 is molded. For molding the raw resin, known molding methods such as injection molding or extrusion molding can be used. In step S02, the cycle time can be shortened by rapidly cooling the mold before removing the molded body of the raw resin after molding. In step S02, the molded body of the raw resin removed from the mold may be subjected to processing to modify its shape, such as cutting or grinding.
[0023] Then, in step S03, the entire surface of the molded body of the raw material resin obtained in step S02 is irradiated with an electron beam. As a result, the electron beam incident on the surface of the molded body of the raw material resin promotes the crystallization of the amorphous portion of the aromatic polyether ketone that constitutes the vicinity of the surface, thereby increasing the degree of crystallinity near the surface.
[0024] As a result, in step S03, a resin molded body is obtained having a surface layer whose crystallinity is increased by electron beam irradiation, and a main body located inside the surface layer and unaffected by electron beam irradiation. In the resin molded body after step S03, the crystallinity immediately after step S02 is maintained in the main body covered by the surface layer.
[0025] Figure 2 shows an example of the infrared absorption spectra of the surface layer and the main body of a resin molded article according to this embodiment. The infrared absorption spectrum of the surface layer is obtained, for example, by measuring the absorbance of the surface of the resin molded article. The infrared absorption spectrum of the main body is obtained, for example, by measuring the absorbance of the cross-section obtained by cutting the resin molded article and exposing the main body.
[0026] In Figure 2, the absorption spectrum of the surface layer is shown by a dashed line, and the absorption spectrum of the main body is shown by a solid line. The intensity B' of peak B is the same in the surface layer and the main body, while the intensity A' of peak A is higher in the surface layer than in the main body. In other words, in the resin molded article according to this embodiment, the ratio of intensities A',B A' / B' is greater in the surface layer than in the main body.
[0027] In a resin molded article, if the energy history applied throughout is uniform, equivalent absorption spectra should be obtained from both the surface and the main body. In this respect, in the resin molded article according to this embodiment, only peak A is higher in the surface than in the main body, indicating that the degree of crystallinity is increased only in the surface.
[0028] In particular, in the molded product of the raw resin immediately after step S02, when the mold is rapidly cooled as described above, the crystallization of the surface layer adjacent to the mold often does not proceed sufficiently, leaving a large amount of amorphous material. In this embodiment, however, the crystallization of the surface layer can be sufficiently advanced in step S03, and furthermore, the degree of crystallinity of the surface layer can be increased compared to that of the main body.
[0029] In the resin molded article according to this embodiment, increasing the degree of crystallinity of the surface layer enhances the mechanical strength near the surface, where large external stresses are likely to be applied. As a result, the resin molded article according to this embodiment can suppress the progression of wear and the occurrence of chipping near the surface, which is composed of the surface layer.
[0030] Furthermore, in the resin molded body according to this embodiment, the shock absorption properties of the main body, which is unaffected by electron beam irradiation, are maintained, so that shocks applied to the surface layer are absorbed effectively. As a result, in the resin molded body according to this embodiment, large localized stresses are less likely to be applied to the surface layer, thus more effectively suppressing the occurrence of damage.
[0031] Thus, in the resin molded body according to this embodiment, the mechanical strength of only the surface layer can be increased by irradiating it with an electron beam, without increasing the mechanical strength of the main body. As a result, in the resin molded body according to this embodiment, an effect of suppressing the occurrence of damage due to the synergistic effect between the surface layer and the main body can be obtained.
[0032] Furthermore, in the resin molded article according to this embodiment, the portion whose degree of crystallinity is changed by electron beam irradiation is limited to the surface layer only, and the degree of crystallinity of the main body, which makes up the majority of the surface layer, is not changed. As a result, in this resin molded article, the amount of shrinkage due to the progression of crystallization after molding is kept small, and the dimensional change from the shape immediately after molding can be kept to a minimum.
[0033] The thickness of the surface layer in the resin molded article according to this embodiment can be appropriately determined depending on the application and other factors. For example, from the viewpoint of more reliably obtaining the above-mentioned effect from the surface layer, it is preferable to set the thickness of the surface layer to 50 μm or more. On the other hand, from the viewpoint of more effectively obtaining the shock absorption performance of the main body, it is preferable to keep the thickness of the surface layer to 700 μm or less.
[0034] The thickness of the surface layer in a resin molded product can be controlled in various ways by changing the electron beam irradiation conditions. However, increasing the thickness of the surface layer requires large-scale equipment, so from the viewpoint of keeping manufacturing costs low without using large-scale equipment, it is preferable to keep the thickness of the surface layer to 700 μm or less.
[0035] Figure 3 is a graph plotting the surface layer ratio A' / B' when the electron beam irradiation dose is varied in step S03. Note that all plots in Figure 3 use the same electron beam irradiation conditions and the same composition of the molded resin material. The zero irradiation dose plot in Figure 4 represents the condition where no electron beam irradiation is used.
[0036] As shown in Figure 3, it can be seen that increasing the electron beam irradiation dose to 50 kGy or more makes it easier to obtain the crystallization-promoting effect described above. On the other hand, if the electron beam irradiation dose is too high, the decomposition of the molecular chains of aromatic polyether ketones will proceed. For this reason, it is preferable to keep the electron beam irradiation dose below 200 kGy.
[0037] Furthermore, in step S03, it is preferable to irradiate the molded body of the raw resin with an electron beam while heating it. This makes it easier to obtain an effect that improves the mechanical strength of the surface layer of the resin molded body, and for example, the fracture properties can be further improved. The temperature of the molded body of the raw resin during electron beam irradiation is preferably, for example, 200°C or higher.
[0038] The resin molded articles according to this embodiment are particularly suitable for application in parts where stress tends to concentrate on the surface. Examples of such parts include gear members, seal rings, thrust washers, and sliding members such as bearings. In resin molded articles configured as sliding members, in addition to suppressing the occurrence of damage, friction loss can also be reduced.
[0039] Figure 4 shows a gear member as an example of the application of the resin molded body as a sliding member according to this embodiment. In a gear member, stress tends to concentrate at the tooth roots of multiple teeth T arranged in series along the outer circumference, but by constructing it as a resin molded body according to this embodiment, the occurrence of chipping of the teeth T can be effectively suppressed.
[0040] [Examples and Comparative Examples] (Brief explanation) Examples and comparative examples of the above embodiments will now be described. In Examples 1 to 8 and Comparative Examples 1 and 2, resin molded articles were prepared, and each sample was evaluated. In Examples 1 to 8, the molded articles of the raw resin were irradiated with an electron beam, whereas in Comparative Examples 1 and 2, the molded articles of the raw resin were not irradiated with an electron beam.
[0041] In Examples 1-3, 5-8, and Comparative Examples 1 and 2, PEEK was used as the raw material resin, specifically Daicel-Evonik's "Vestakeep® 4000G". In Example 4, PEK was used as the raw material resin, specifically VICTREX's "VICTREX® HT". In Example 5, 20% by weight of carbon fiber and 10% by weight of PTFE were added as additives to the raw material resin.
[0042] (Examples 1-5) In Examples 1-5, electron beam irradiation was performed at room temperature. In Examples 1-3, electron beam irradiation was performed at different doses. Specifically, in Example 1, the irradiation dose was 50 kGy, in Example 2, it was 100 kGy, and in Example 3, it was 200 kGy. In Example 4, the irradiation dose was 100 kGy, and in Example 5, it was 200 kGy.
[0043] In all of Examples 1 to 5, the "EC300 / 30 / 30mA" manufactured by Iwasaki Electric was used to irradiate the molded resin material with electron beams. In all of Examples 1 to 4, the electron beam irradiation conditions were set to an acceleration voltage of 290kV, a beam current of 6.3mA, and a transport speed of 8m / min.
[0044] The samples in Examples 1 to 5 all shared the same configuration except for the one described above. For Comparative Example 1, the molded resin of the raw material used in Examples 1 to 3 before electron beam irradiation was used. The absorbance of the surface and main body of the samples in Examples 1 to 5 and Comparative Example 1 was measured using an infrared spectrophotometer. The absorbance was measured using the ATR method with a Ge lens using a JASCO FT / IR-4600 Fourier transform infrared spectrophotometer.
[0045] The ratio A' / B' was calculated from the infrared absorption spectra obtained by absorbance measurements. Table 1 shows the ratio A' / B' of the surface layer and the main body for Examples 1-5 and Comparative Example 1. In Comparative Example 1, the ratio A' / B' was equal in the surface layer and the main body, whereas in Examples 1-5, the ratio A' / B' was higher in the surface layer than in the main body.
[0046] Next, wear resistance tests were conducted on each sample related to Examples 1-5 and Comparative Example 1 to evaluate their wear characteristics. A reciprocating sliding friction wear testing machine, "TRIBOGEAR TYPE-14," manufactured by Shinto Kagaku, was used for the wear resistance tests. For the wear resistance tests, each sample was shaped into a strip measuring 10 mm × 80 mm × 0.1 mm.
[0047] Furthermore, in the abrasion resistance tests for each sample, a conical indenter (sapphire, 90° internal angle, 0.05 mm tip radius of curvature) was used, with a load of 150 gf, a sliding speed of 300 mm / min, a travel distance of 10 mm, and all other conditions being the same. For each sample, "OK" or "NG" was determined based on the presence or absence of abrasion of 100 μm or more.
[0048] Table 1 shows the results for each number of reciprocations (10, 20, 30, 40, and 50) for Examples 1-5 and Comparative Example 1. As shown in Table 1, all samples in Examples 1-5 obtained good results up to 50 reciprocations, and showed higher wear resistance than the sample in Comparative Example 1, which failed after 40 reciprocations.
[0049] Next, tensile tests were performed on each sample from Examples 1-3 and Comparative Example 1 to evaluate their fracture characteristics. A Shimadzu AGX tensile tester was used for the tests. For the tensile tests, each sample was shaped like an A12 dumbbell, conforming to JIS K7139 (2009). In all tensile tests, the tensile speed was set to 10 mm / min, and all other conditions were the same.
[0050] As a result, Table 1 shows the percentage change in breaking strength (%) for Examples 1 to 3 compared to Comparative Example 1. As shown in Table 1, the samples in Examples 1 to 3 all have higher breaking strength than the sample in Comparative Example 1, indicating that the high breaking strength is achieved through the action of the surface layer.
[0051] Next, tear tests were performed on each sample from Examples 1-3 and Comparative Example 1 to evaluate their fracture characteristics. A Shimadzu AGX tear tester was used. For the tear tests, each sample was prepared as a strip measuring 10 mm × 80 mm × 0.1 mm (with a 1 mm notch). In all tear tests, the tensile speed was set to 10 mm / min, and all other conditions were the same.
[0052] As a result, Table 1 shows the percentage change in tear stroke for Examples 1 to 3 compared to Comparative Example 1. As shown in Table 1, the tear strokes in all of the samples from Examples 1 to 3 were larger than those in the Comparative Example, indicating that the larger tear strokes were obtained due to the action of the surface layer.
[0053] Next, friction tests were conducted on each sample related to Examples 1-3 and Comparative Example 1 to evaluate their frictional properties as sliding members. A reciprocating sliding friction and wear testing machine, "TRIBOGEAR TYPE-14," manufactured by Shinto Kagaku, was used for the friction tests. For the friction tests, each sample was shaped like a strip measuring 10 mm × 80 mm × 0.1 mm.
[0054] Furthermore, in the friction tests for each sample, a spherical indenter (made of stainless steel, φ4 mm) was used, with a load of 100 gf, a sliding speed of 600 mm / min, and a travel distance of 20 mm, with all other conditions being the same. In addition, grease (Sumitec F931) was used to lubricate the sliding surface on which the indenter slid in each sample.
[0055] As a result, Table 1 shows the percentage change in the coefficient of dynamic friction for Examples 1 to 3 compared to Comparative Example 1. As shown in Table 1, the samples in Examples 1 to 3 all have lower coefficients of dynamic friction than the sample in the Comparative Example, indicating that high sliding characteristics as sliding members are obtained due to the action of the surface layer.
[0056] Next, gear fatigue tests were conducted on each sample related to Examples 1-3 and Comparative Example 1 to evaluate their fatigue characteristics as gear components. In the gear fatigue tests, each sample was given a gear shape. In the gear fatigue tests for each sample, a gear component (made of S45C) was used as the mating material, and the samples were rotated while meshed with the mating material.
[0057] Furthermore, in the gear fatigue tests for each sample, the rotational speed was set to 2000 rpm, the torque to 6 N·m, and all other conditions were the same. The lubrication condition between each sample and the mating material during rotation was kept dry. For each sample, "OK" or "NG" was determined based on whether or not there was any chipping of the teeth after 200,000 rotations.
[0058] Table 1 shows the results of gear fatigue tests for Examples 1-3 and Comparative Example 1. As shown in Table 1, no tooth chipping occurred in any of the samples from Examples 1-3, whereas tooth chipping occurred in the sample from Comparative Example 1. This indicates that Examples 1-3 exhibit high fatigue characteristics as gear components.
[0059] [Table 1]
[0060] (Examples 6-8) In Examples 6-8, the sample temperature during electron beam irradiation was changed from that in Example 2. Specifically, in Example 6, the sample temperature was 200°C, in Example 7, it was 250°C, and in Example 8, it was 300°C. In addition, in all Examples 6-8, the electron beam irradiation dose was 100 kGy, the same as in Example 2.
[0061] In other words, in Examples 6 to 8, the electron beam irradiation conditions differ from those in Example 2, where the sample temperature was room temperature, in that the sample was heated. Tensile tests were performed on each sample in Examples 6 to 8 to evaluate the fracture characteristics. The conditions for the tensile tests were the same as those for Examples 1 to 3 and Comparative Example 1 described above.
[0062] As a result, Table 2 shows the percentage change in fracture strength (%) for Examples 2, 6-8 compared to Comparative Example 1. As shown in Table 2, it can be seen that in all of the samples of Examples 6-8, which were irradiated with an electron beam while being heated, higher fracture strengths were obtained than in the sample of Example 2.
[0063] [Table 2]
[0064] Furthermore, a sample relating to Comparative Example 2 was prepared by subjecting the sample relating to Comparative Example 1 to heat treatment (annealing) at 300°C. In other words, the sample relating to Comparative Example 2 is similar to the sample relating to Example 8 in that the molded body of the raw resin is heated to 300°C, but it differs from the sample relating to Example 8 in that it is not irradiated with an electron beam.
[0065] A tensile test similar to that in Example 8 was performed on the sample related to Comparative Example 2. Table 3 shows the percentage change (%) in the breaking strength of Example 8 compared to Comparative Example 2. As shown in Table 3, it can be seen that the sample related to Example 8, which was heated while being irradiated with an electron beam, obtained a higher breaking strength than the sample related to Comparative Example 2, which was simply heated.
[0066] [Table 3]
[0067] [Other embodiments] Although embodiments of the present invention have been described above, it goes without saying that the present invention is not limited to the embodiments described above and can be modified in various ways.
[0068] For example, in the present invention, the method for increasing the crystallinity of the surface layer of the aromatic polyether ketone molded body is not limited to electron beam irradiation. Other methods for increasing the crystallinity of the surface layer include, for example, laser irradiation, UV irradiation, excimer irradiation, plasma irradiation, corona irradiation, flame treatment, and chemical treatment.
Claims
1. The device includes a main body and a surface layer that covers the main body. In both the main body and the surface layer, the wave number is 1295 to 1340 cm when measured by an infrared spectrophotometer. -1 Peak A appears in the range of wave numbers 1265 to 1295 cm -1 and a peak B appearing in the range of A ratio A' / B' of an intensity A' of the peak A to an intensity B' of the peak B is higher in the surface layer portion than in the main body portion. Aromatic polyether ketone molding.
2. The aromatic polyether ketone molded article according to claim 1, Formed from at least one of polyetheretherketone and polyetherketone Aromatic polyether ketone molding.
3. The aromatic polyether ketone molded article according to claim 1, Made from aromatic polyetherketone containing additives Aromatic polyether ketone molding.
4. The aromatic polyether ketone molded article according to any one of claims 1 to 3, Configured as a sliding member Aromatic polyether ketone molding.
5. The aromatic polyether ketone molded article according to claim 4, Configured as a gear member Aromatic polyether ketone molding.
6. Measurements using an infrared spectrophotometer reveal that the wavenumber is 1295 to 1340 cm -1 Peak A appears in the range of wave numbers 1265 to 1295 cm -1 A step of producing a molded product having an infrared absorption spectrum including a peak B appearing in the range of a step of irradiating the surface of the molded body with an electron beam to increase a ratio A' / B' of an intensity A' of the peak A to an intensity B' of the peak B in a surface layer portion of the molded body; A method for producing an aromatic polyether ketone molded article comprising the steps of:
7. A method for producing the aromatic polyether ketone molded article according to claim 6, comprising the steps of: In the step of irradiating the electron beam, the molded body is heated. A method for producing an aromatic polyether ketone molded article.